2019
DOI: 10.1021/acs.jpcc.9b00378
|View full text |Cite
|
Sign up to set email alerts
|

Salinity-Induced Reduction of Interfacial Energies and Kinetic Factors during Calcium Carbonate Nucleation on Quartz

Abstract: Nucleation is a crucial nanoscale process during the formation of new phases. This study employs CaCO 3 nucleation on quartz as an example system and investigates the effects of salinity on thermodynamic and kinetic factors in CaCO 3 nucleation. In situ grazing incidence small-angle X-ray scattering was used to obtain the nucleation rates of CaCO 3 at different supersaturations (IAP/K sp(calcite) = 10 1.40 to 10 2.00 ) and NaCl-adjusted ionic strengths (i.e., salinities). From a salinity value of 0.15 to 0.85 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 38 publications
(95 reference statements)
1
35
0
Order By: Relevance
“…In comparison to the spherulites produced in low salinity experiments (Figure 3), high salinity environments appear to generate smaller particles, but not shrubby calcite. This emergence of smaller mineral particles at extreme salinity could be due to, first, faster nucleation rates on account of a decreased water‐CaCO 3 interfacial energy with increasing ionic strength assuming the classical nucleation model (Li et al, 2019). However, it is also established that the pathways of CaCO 3 nucleation involve ion pairs, pre‐nucleation clusters, liquid condensed phases and amorphous precursors (De Yoreo et al, 2015; Gebauer, 2018; Rodríguez‐Navarro et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to the spherulites produced in low salinity experiments (Figure 3), high salinity environments appear to generate smaller particles, but not shrubby calcite. This emergence of smaller mineral particles at extreme salinity could be due to, first, faster nucleation rates on account of a decreased water‐CaCO 3 interfacial energy with increasing ionic strength assuming the classical nucleation model (Li et al, 2019). However, it is also established that the pathways of CaCO 3 nucleation involve ion pairs, pre‐nucleation clusters, liquid condensed phases and amorphous precursors (De Yoreo et al, 2015; Gebauer, 2018; Rodríguez‐Navarro et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Alternation between micritic and microsparitic laminae is attributed to a variation in the predominance of nucleation and crystallization processes during the growth of the stromatolite (Riding, 2000;Dupraz et al 2009). This can be produced by different factors, such as the hydrodynamic energy, changes in the precipitation rate, changes in Three-dimensional Yacoraite Formation stromatolites, Argentina saturation, level of organic activity, and/or fluctuation of carbonate and calcium concentration (Giuffre et al 2013;Dobberschütz et al 2018;Li & Jun, 2019).…”
mentioning
confidence: 99%
“…Both increasing salinity and temperature have had a negative effect on soil strength for calcium mineral stabilised soils, which has been a considerable challenge to developing a sustainable approach in arid environments. Higher salt 55 concentration and temperature 56 are responsible for nucleating smaller calcium mineral crystals, which result in weaker inter-particle connections between soil particles, and therefore a lower bearing capacity at the macro-scale. For example, Chen et al 56 found a 60% reduction in strength for calcium carbonate stabilised soils, on increasing curing temperatures from 25 to 40 , with a significant reduction in crystal size (15–20 m to 2–5 m).…”
Section: Discussionmentioning
confidence: 99%